2012
DOI: 10.1007/978-1-4614-5894-4_2
|View full text |Cite
|
Sign up to set email alerts
|

Prominin-2 and Other Relatives of CD133

Abstract: Several molecules related to prominin-1/CD133, which was first characterized as a marker of mouse neuroepithelial stem cells and human hematopoietic stem cells, have been identified in various species. In mammals, a second prominin gene, prominin-2, has been identified and characterized, whereas in nonmammalian species, up to three prominin genes are potentially expressed. The structural similarities between prominin-1 and prominin-2 are, to some extent, reflected by their biochemical properties; both proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Moreover, PROM1+ ovarian CSCs are highly tumorigenic, chemoresistant, and metastatic and they promote the adhesion capabilities of the ovarian cancer metastatic niche [57]. In contrast, our analysis showed that PROM2 is overexpressed in breast and lung cancers, and this result is in agreement with those of previous genome profiling studies and studies on expressed sequence tag (EST) clones deposited in the GenBank database [58,59]. Thus, these results imply that prominins may be either oncogenes or tumor suppressor genes, depending on the type of cancer.…”
Section: Prominin Mrna Expression Analysissupporting
confidence: 91%
“…Moreover, PROM1+ ovarian CSCs are highly tumorigenic, chemoresistant, and metastatic and they promote the adhesion capabilities of the ovarian cancer metastatic niche [57]. In contrast, our analysis showed that PROM2 is overexpressed in breast and lung cancers, and this result is in agreement with those of previous genome profiling studies and studies on expressed sequence tag (EST) clones deposited in the GenBank database [58,59]. Thus, these results imply that prominins may be either oncogenes or tumor suppressor genes, depending on the type of cancer.…”
Section: Prominin Mrna Expression Analysissupporting
confidence: 91%
“…It is the first member of the pentaspan membrane glycoprotein prominin family, which is expressed throughout the animal kingdom [3][5]. Human prominin -1 as detected by the widely used monoclonal antibody (mAb) AC133 [6] marks numerous somatic stem and progenitor cells originating from various tissues and organs [4], [7][10].…”
Section: Introductionmentioning
confidence: 99%
“…Although both genes display a higher degree of compactness compared to prom1 (Table S1), they do not show a conserved synteny (11). Still, prom3 might have evolved from the same ancestral locus as prom2 generated during the first round of vertebrate genome duplication (11,12,91).…”
Section: Discussionmentioning
confidence: 99%